2019
DOI: 10.1016/j.fusengdes.2019.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Design of model tokamak particles for future toxicity studies: Morphology and physical characterization

Abstract: During ITER operation, it is expected that the large panel of plasma-wall interactions triggers the production of dust particles, potentially loaded with tritium present nearby. Tritium (T) inventory in the various materials, such as tungsten (W), is of prime importance for the safety assessment of a Tokamak machine, and it is even more crucial when considering dispersible matters like dusts: in case of a Loss Of Vacuum Accident (LOVA), dusts may form aerosols containing tritium and activation products that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…A detailed physico-chemical characterization of the ITER-like plasma and laser W-NPs, in their powder form, was already presented [15,16,19] and is here summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed physico-chemical characterization of the ITER-like plasma and laser W-NPs, in their powder form, was already presented [15,16,19] and is here summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Even if we can identify similarities between the outcome of previous studies on W and our data, there are some important differences that we think are pivotal in understanding our results and the mechanisms by which W results toxic. First of all, our bench produced plasma and laser ITER-like W-NPs display peculiar physico-chemical properties [15,16,17]. More in detail, although they are metallic W-NPs, XAS and helium pycnometer analysis have shown that a significant fraction of tungsten oxide (WO x ) is present and it could participate in the toxicity of the particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…W NPs obtained by MSGA were reported for the first time by us in [28]. Further works were related to studies regarding tritium absorption and retention [39,40] in this material and W NP cytotoxicity [41][42][43]. These experiments will be also presented briefly in this chapter.…”
Section: Tungsten Nanoparticles: Their Applications and Methods For Tmentioning
confidence: 99%
“…A full dissolution was obtained after 2 to 60 days of exposure to 100-200 nm W particles depending on the dust type [16,17]. In addition, a full dissolution of large W particles (up to 7 µm of diameter) was also observed.…”
Section: Toxicity Studiesmentioning
confidence: 99%